Management Accounting: Its Goals and Features An Overview - Kumar, Dr. Rakesh (Innovative Research Thoughts, 2021)
When it comes to managing performance and making informed decisions, management accounting is crucial. Management accounting is defined, with its aims, characteristics, and guiding principles laid out in this article. We delve into the main goals of management accounting, which include helping with strategic decision-making, improving planning and control, and giving managers timely and appropriate information. We go on to talk about what makes management accounting unique, including how it prioritises internal users, looks forward, and is very adaptable. Cost accounting, budgeting, performance assessment frameworks, and variance analysis tools are some of the important elements of management accounting systems that we also emphasise. To increase operational efficiency, boost decision-making processes, and accomplish strategic objectives, organisations may successfully employ management accounting by knowing its aims and characteristics. In order to help organisations succeed in today's fast-paced business world, this article will give a general outline of management accounting and why it's important.